Evalution of Fixed Assets Management - A.Naresh, .I.Satyanarayana, N.B.C.Sidhu (International Journal of Scientific Research and Management (IJSRM), 2015)
Fixed assets, also known as "tangible assets “or property, plant, and equipment (PP&E), is a term used in accounting for assets and property that cannot easily be converted into cash. This can be compared with current assets such as cash or bank accounts, which are described as liquid assets. In most cases, only tangible assets are referred to as fixed. AS 16 (International Accounting Standard) defines Fixed Assets as assets whose future economic benefit is probable to flow into the entity, whose cost can be measured reliably. Moreover, a fixed/non-current asset can also be defined as an asset not directly sold to a firm's consumers/end-users. As an example, a baking firm's current assets would be its inventory (in this case, flour, yeast, etc.), the value of sales owed to the firm via credit (i.e. debtors or accounts receivable), cash held in the bank, etc. Its non-current assets would be the oven used to bake bread, motor vehicles used to transport deliveries, cash registers used to handle cash payments, etc. While these non-current assets have value, they are not directly sold to consumers and cannot be easily converted to cash. These are items of value that the organization has bought and will use for an extended period of time; fixed assets normally include items such as land and buildings, motor vehicles, furniture, office equipment, computers, fixtures and fittings, and plant and machinery. These often receive favourable tax treatment (depreciation allowance) over short-term assets. It is pertinent to note that the cost of a fixed asset is its purchase price, including import duties and other deductible trade discounts and rebates. In addition, cost attributable to bringing and installing the asset in its needed location and the initial estimate of dismantling and removing the item if they are eventually no longer needed on the location. The primary objective of a business entity is to make profit and increase the wealth of its owners. In the attainment of this objective it is required that the management will exercise due care and diligence in applying the basic accounting concept of “Matching Concept”. Matching concept is simply matching the expenses of a period against the revenues of the same period.